PENGARUH KONFLIK PERAN GANDA, STRES KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN WANITA PT.STARLIGHT GARMENT SEMARANG (STUDI KASUS KARYAWAN KARYAWAN WANITA BAGISAN FINISHING) - Nugraheni, Wahyu Fitri; Nurmiyati, Nurmiyati; Rakhman, Muhammad Arif (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2024)
Human resources are one of the important factors in a company or organization, individuals become the main driving force in the running of the company to achieve company goals. Decreased employee performance can be influenced by several things such as female workers who experience dual role conflict, they have to divide their time between family and work, the targets given are too many and the absence of bonuses makes work motivation decrease. The purpose of this study was to determine the effect of dual role conflict, work stress and motivation on the performance of female employees of PT Starlight Garment Semarang. The research methodology used is quantitative, this method is used through a survey, namely the data collection method. The data collection technique uses Purposive Sampling technique, the sampling technique used is using non probability sampling. Data collection techniques using questionnaires processed with the SPSS version 25 application. The data analysis method used in this study is to use: 1. instrument test consists of validity test and reliability test, 2. correlation test consists of simple correlation and multiple correlation, 3. regression test consists of simple regression and multiple regression, 4. determination test, 5. t test, 6. F test. Keywords: Dual Role Conflict, Work Stress, Motivation and Employee Performanc